STABILITY OF AFLATOXINS IN NATURALLY CONTAMINATED PISTACHIO NUTS INCORPORATED IN SOME LOCAL SWEET DISHES OF PAKISTAN (Biological Sciences - PJSIR, 2002)
The possible effects of conventional Pakistani cooking practices on the integrity and stability of naturally occurring aflatoxins in a complex food matrix of sweet dishes were observed . Three conventional local sweet dishes of pistachio nuts, naturally contaminated with different levels of aflatoxins were studied. Prior to cooking there was a decrease in recovery of aflatoxins from the various types of food matrices in all the three sweet dishes. Some variations were observed from the initial contents and the recovery from the precooked contents of naturally contaminated aflatoxins of two sweet dishes. Some variation in the recovery of aflatoxins in the milk based sweet dish was also   observed.